Is there a Peaceful Economic Solution to the Tensions between the People’s Republic of China and the United States of America about Taiwan? (Global Journal of Human-Social Science, 2024)
As the tensions between the People s Republic of China PRC and the United States of America USA mount about the desires of the PRC to incorporate Taiwan into its political and economic structure is there no alternatives to war between the PRC and USA over the issue other than the forceful political takeover of Taiwan by the PRC Is the USA caught like the British and French in 1938 with no choice other than appeasement or war The author believes there is a feasible alternative namely the encouragement of the PRC and Taiwan to form a Greater Chinese Common Market similar the original European Common Market where each country retains its political sovereignty but with a joint set of economic trade and investment policies This approach has clearly worked in Europe with Germany no longer being a war threat but instead playing a key leadership role in the European Common Market ECM and the subsequent European Union EU It is not clear whether this economic Greater China is enough to satisfy the desires of the PRC government for a cultural Greater China and political Greater China that would result from the forcible takeover of Taiwan by the PRC but the formation of the GCCM would be possible without a war in the Taiwan Straits and could eventually lead to the political integration of Taiwan into the PRC